Elimination of UAV’s as reason for war, risks of escalation of conflict and intervention: analogizing recent cases 2010-2019 - Kutukovs, Igors (Riga Graduate School of Law, 2019)
The current international situation is characterized by growing tension in relations between many countries, the presence of disputed territories and hot spots. The development of technology has led to the emergence of various types of unmanned aerial vehicles, as well as their increasing use for both civil and military purposes. A qualitative analysis of five conflict situations in which incidents related to the destruction of drones occurred demonstrated the advantages of their use (reduction of possible human losses, cost reduction, the possibility of quick response, etc.), as well as the existing imbalance in the legal and political foundation and practical use. It is clear that the use of drones does not lead to de-escalation of the conflict, but in most cases it does not change the direction of the conflict and does not lead to widespread escalation and hostilities.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Drones; Weapons; Conflict resolution